Fishing for Answers: The Implications of Environmental Defence Society v King Salmon - Milne, Eleanor (Victoria University of Wellington Law Review, 2015)
The Supreme Court’s decision in Environmental Defence Society Inc v King Salmon Co Ltd, of early 2014, is a positive development in New Zealand’s resource management law. The decision endorses the environmental bottom line approach and prohibits the use of the purpose section of the Resource Management Act 1991 when making operative decisions. If the decision is applied widely, there is scope for some of the problems with the resource management law framework to be addressed. In particular, the decision has the potential to reduce the uncertainty within the system caused by the lack of central government direction and the inconsistencies between local governments, and the issues when applying the purpose of the Resource Management Act. The article also analyses the effect of the decision on the reforms to the Resource Management Act that were proposed in 2014, and concludes that the arguments for the reforms are now much weaker.